Does television viewing predict dietary intake five years later in high school students and young adults? - Neumark-Sztainer Dianne; Nelson Melissa C; Larson Nicole I; Barr-Anderson Daheia J; Story Mary (BMC, 2009)
Abstract Background Prior research has found that television viewing is associated with poor diet quality, though little is known about its long-term impact on diet, particularly during adolescence. This study examined the associations between television viewing behavior with dietary intake five years later. Methods Survey data, which included television viewing time and food frequency questionnaires, were analyzed for 564 middle school students (younger cohort) and 1366 high school students (older cohort) who had complete data available at Time 1 (1998-1999) and five years later at Time 2 (mean age at Time 2, 17.2 ± 0.6 and 20.5 ± 0.8 years, respectively). Regression models examined longitudinal associations between Time 1 television viewing behavior and Time 2 dietary intake adjusting for sociodemographic characteristics, Time 1 dietary intake, and Time 2 total daily energy intake. Results Respondents were categorized as limited television users (<2 hours/daily), moderately high television viewers (2-5 hours/daily), and heavy television viewers (≥5 hours/daily). Among the younger cohort, Time 1 heavy television viewers reported lower fruit intake and higher sugar-sweetened beverage consumption than the other two groups. Among the older cohort, watching five or more hours of television per day at Time 1, predicted lower intakes of fruits, vegetables, whole grain and calcium-rich foods, and higher intakes of trans fat, fried foods, fast food menu items, snack products, and sugar-sweetened beverages (products commonly advertised on television) five years later. Conclusion Television viewing in middle and high school predicted poorer dietary intake five years later. Adolescents are primary targets of advertising for fast food restaurants, snack foods, and sugar-sweetened beverages, which may influence their food choices. Television viewing, especially during high school, may have long-term effects on eating choices and contribute to poor eating habits in young adulthood.